Dental Considerations for Age Determination in humans - Althaf Hussain Chalkoo (Wolters Kluwer Medknow Publications, 2006)
The basis for dental identification is the theory that human dentition is never the same in any two individuals. Although teeth are resistant to environmental insults during life they are susceptible to physiological and pathological changes. As a result teeth may have restorations which may alter their original morphology. Dental age estimation makes use of morphologic, radiographic, histological and biochemical methods- to estimate age dependant changes in teeth.